Az Osztrák-Magyar Monarchia : a geopolitikai kényszertől a világpolitikai feleslegességig - Hajdú, Zoltán (Közép-Európai Közlemények, 2009)
The Austro–Hungarian Monarchy (1867–1918) was formed on the basis of European geopolitical constrain, and she played a great power role between 1867–1918. At the birth of Monarchy the outher influences were dominated. After the Great War the Monarchy turned to be superfluous from the point of World political situation. The half century history of Monarchy basically influenced the European political and historical thinking.